Implementasi Kebijakan Alokasi Anggaran Pendidikan dalam Meningkatan Mutu Pendidikan Dasar Sembilan Tahun di Kota Palembang - Sulaiman, Muhammad Fahmi (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT Budgetary policy education is run in local government in the city of Palembang. This research is to find out the problems arising from the policies made and to identify weaknesses, so that the impact of the budget allocation for the quality of education in the city of Palembang will run well and achieve the goals that have been set to implement and improve the quality of education in particular association as it normative documents listed on regional planning for the necessary implementation of a policy that allows nine years of basic education (9-year compulsory basic education) in Palembang can run well and quality.This study used a qualitative approach to policy analysis method or methods of post policy analysis, while the technique of data collecting documentation study, interview and observation. Results and conclusions of the study show that the city of Palembang is already running a local autonomy in education well with 51.8% of the total education spending APBDnya.The amount of the allocation of indirect spending compared to spending langsung.Ada realization of direct expenditure budget allocation that is less effective and efficient. Impact of Policy Implementation in 2012 Education Budget Allocation Budget allocation priority on basic education in Palembang with the goal of Increasing the quality of public education and increasing the number of qualified teachers S1 / D-IV.